Effect of constraint-induced movement therapy on lower extremity motor dysfunction in post-stroke patients: A systematic review and meta-analysis - Zhou, Mingze; Tu, Yang; Cui, Jiarui; Gao, Ping; Yi, Ting; Wang, Jun; Hao, Qinghong; Li, Hui; Zhu, Tianmin (Frontiers in Neurology, 2022)
Objective: Constraint-induced movement therapy (CIMT) is a common treatment for upper extremity motor dysfunction after stroke, but whether it can effectively improve the lower extremity motor function in patients with stroke remains controversial. The purpose of this systematic review is to comprehensively study the current evidence and evaluate the effectiveness of CIMT in the treatment of post-stroke lower extremity motor dysfunction. Methods: A comprehensive search of eight electronic databases (PubMed, Embase, The Cochrane Library, Web of Science, CBM, CNKI, WAN FANG and VIP) was performed to find and pinpoint all RCTs related to this study. The effectiveness of CIMT in the treatment of post-stroke lower extremity motor dysfunction was evaluated based on mean difference and corresponding 95% confidence interval (95% CI). Methodological quality was assessed based on the Cochrane Bias Risk Assessment Tool. After extracting the general information, mean and standard deviation of the included studies, meta-analysis was conducted by RevMan 5.3 and Stata 16.0. The primary indicator was the Fugl-Meyer Assessment scale on lower limbs (FMA-L). BBS, 10MWT, Gait Speed, 6MWT, FAC, TUGT, Brunnstrom stage of lower limb function, Weight Bearing, MBI, FIM, SSQOL, WHOQOL, and NIHSS were used as the secondary indicators. Results: A total of 343 relevant studies were initially identified, and 34 of them met the inclusion and exclusion criteria after the screening, containing 2008 patients. The results indicated that there were significant improvements in primary indicator (FMA-L) scores among those treated with CIMT than those not: CIMT compared with conventional physiotherapy, 3.46 (95% CI 2.74-4.17, P<0.01, I2=40%); CIMT plus conventional physiotherapy compared with conventional physiotherapy, 3.83 (95% CI 2.89-4.77, P<0.01, I2=54%); and CIMT plus western medicine therapy compared with western medicine therapy, 3.50 (95% CI 1.08-5.92, P<0.01), and the secondary indicators showed the same tendency. Conclusion: Our present study showed that CIMT could effectively improve the lower extremity motor dysfunction of post-stroke patients, despite the high heterogeneity among the eligible studies.